Advances in theoretical calculations of MXenes as hydrogen and oxygen evolution reaction (water splitting) electrocatalysts. (27th September 2022) - Hou, Pengfei; Tian, Yumiao; Jin, Di; Liu, Xiaochun; Xie, Yu; Du, Fei; Meng, Xing
Abstract: Two-dimensional transition metal carbides/nitrides/carbon nitrides (MXenes) have great potential to be excellent H and O evolution reaction (HER and OER) electrocatalysts due to their special properties, such as large specific surface area, good electrical conductivity, and abundant active sites. Researchers have carried out many types of investigations on MXenes as HER and OER electrocatalysts. So far, great progress has been made in screening MXenes as HER and OER electrocatalysts, in which the theoretical calculation method plays an important role. In the present study, we briefly summarize the progress regarding theoretical calculations of MXenes as HER and OER electrocatalysts. First, we introduce the standard computational methods and basic mechanisms of HER and OER. We then present some recent studies of theoretical calculations and experiments combined with theoretical calculations. Finally, some specific perspectives are provided for the future development of MXenes as excellent HER and OER electrocatalysts. We believe theoretical computational studies of MXenes as HER and OER electrocatalysts may flourish by considering the natural reaction environment and electrochemical kinetic processes, the proposal of more activity descriptors, close integration of theory and experiments, and the development of advanced calculation methods.